Clumping factor A, von Willebrand factor‐binding protein and von Willebrand factor anchor Staphylococcus aureus to the vessel wall. (23rd March 2017) - Claes, J.; Liesenborghs, L.; Peetermans, M.; Veloso, T. R.; Missiakas, D.; Schneewind, O.; Mancini, S.; Entenza, J. M.; Hoylaerts, M. F.; Heying, R.; Verhamme, P.; Vanassche, T.
Abstract : Essentials Staphylococcus aureus ( S. aureus ) binds to endothelium via von Willebrand factor (VWF). Secreted VWF‐binding protein (vWbp) mediates S. aureus adhesion to VWF under shear stress. vWbp interacts with VWF and the Sortase A‐dependent surface protein Clumping factor A (ClfA). VWF‐vWbp‐ClfA anchor S. aureus to vascular endothelium under shear stress. Summary: Objective: When establishing endovascular infections, Staphylococcus aureus (S. aureus) overcomes shear forces of flowing blood by binding to von Willebrand factor (VWF). Staphylococcal VWF‐binding protein (vWbp) interacts with VWF, but it is unknown how this secreted protein binds to the bacterial cell wall. We hypothesized that vWbp interacts with a staphylococcal surface protein, mediating the adhesion of S. aureus to VWF and vascular endothelium under shear stress. Methods: We studied the binding of S. aureus to vWbp, VWF and endothelial cells in a micro‐parallel flow chamber using various mutants deficient in Sortase A (SrtA) and SrtA‐dependent surface proteins, and Lactococcus lactis expressing single staphylococcal surface proteins. In vivo adhesion of bacteria was evaluated in the murine mesenteric circulation using real‐time intravital vascular microscopy. Results: vWbp bridges the bacterial cell wall and VWF, allowing shear‐resistant binding of S. aureus to inflamed or damaged endothelium. Absence of SrtA and Clumping factor A (ClfA) reduced adhesion of S. aureus to vWbp, VWF and activated endothelial cells. ADAMTS‐13 and an anti‐VWF A1 domain antibody, when combined, reduced S. aureus adhesion to activated endothelial cells by 90%. Selective overexpression of ClfA in the membrane of Lactococcus lactis enabled these bacteria to bind to VWF and activated endothelial cells but only in the presence of vWbp. Absence of ClfA abolished bacterial adhesion to the activated murine vessel wall. Conclusions: vWbp interacts with VWF and with the SrtA‐dependent staphylococcal surface protein ClfA. The complex formed by VWF, secreted vWbp and bacterial ClfA anchors S. aureus to vascular endothelium under shear stress.